TEA TECHNOLOGY AND ITS PROCESS: A REVIEW - Luan Ramos da Silva; Danielle Marques Vilela (UNINGÁ Review, 2019)
Tea, a beverage made by leaves of Camelia sinensis plants, is one of the most consumed beverages in the world. Besides its great flavor and aroma for the human palate, tea is a source of many chemical compounds, which has medicinal qualities. It originated in the year 2738 BC, in China, the largest producer and consumer country of tea. Plants of C. sinensis have a good capacity of adaptation in places with climate variation; also, thecomposition of its leaves is different as a function of its management. Among many kinds of tea, black and oolong tea are obtained by fermentation which consist basically of an enzymatic oxidation process without microorganisms. During its processing, oxidation and polymerization occur, resulting in changes in the leaves to guarantee a final product with adequate flavor, aroma and composition for human consumption.